2015
DOI: 10.1039/c4ta06124a
|View full text |Cite
|
Sign up to set email alerts
|

Dual template-directed synthesis of SAPO-34 nanosheet assemblies with improved stability in the methanol to olefins reaction

Abstract: Hierarchical SAPO-34 catalysts with different morphologies were synthesized by using dual template [3-(trimethoxysilyl)propyl]octadecyldimethylammonium chloride and diethylamine. Because of its optimal porosity and acidity, hierarchical SAPO-34 exhibited excellent catalytic performance in the MTO reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(88 citation statements)
references
References 44 publications
3
84
1
Order By: Relevance
“…For the case of SAPO-34 zeolite and TiO 2 /SAPO-34 composite, the TGA signal of the zeolite is identical to those obtained in the literature [51,52]. It is clear that the weight loss stages of TiO 2 /SAPO-34 are different compared to the SAPO-34, which is probably due to the presence of TiO 2 nanostructures on the surface of SAPO-34.…”
Section: Photocatalytic Degradation Of Mbsupporting
confidence: 67%
“…For the case of SAPO-34 zeolite and TiO 2 /SAPO-34 composite, the TGA signal of the zeolite is identical to those obtained in the literature [51,52]. It is clear that the weight loss stages of TiO 2 /SAPO-34 are different compared to the SAPO-34, which is probably due to the presence of TiO 2 nanostructures on the surface of SAPO-34.…”
Section: Photocatalytic Degradation Of Mbsupporting
confidence: 67%
“…[15][16][17] Recently, more efforts have been made towards the "direct synthesis" of hierarchical zeolites through soft-templating routes, [18][19][20][21] which can achieve greater mesoporosity, more precise control of pore size, and higher zeolite structure integrity compared with "post-treatment" methods. Hierarchical zeolites prepared by different methods have been tested as catalysts for various reactions, and typically, they exhibit higher catalytic activities (especially when the reactant molecules are bulky) , [22][23] longer lifetimes, [24][25] slower coke formation rates, 26 and altered product selectivities 27 compared to conventional zeolites with the same framework types. For example, we recently reported that a non-surfactant cationic polymer can act as a dual template to synthesize hierarchical zeolite Beta.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the longer the chain of PEG is, the fewer strong acid sites will occur. As the strong acid site corresponds to the incorporation of silicon into the framework of SAPO-34 catalyst [35,36], we can speculate that the long chain of PEG can hinder silicon from incorporating into the framework to some extent.…”
Section: Resultsmentioning
confidence: 99%